2018
DOI: 10.18203/2320-1770.ijrcog20183304
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on outcomes of postpartum intrauterine contraceptive device including safety, efficacy and expulsion at GMERS Medical College, Dharpur-Patan, Gujarat, India

Abstract: INTRODUCTIONPostpartum period is a very vulnerable period both for women and infant. Initiation of contraception during this period is important to prevent unintended pregnancy and short birth intervals. It can avert more than 30% of maternal deaths and 10% of child mortality. Pregnancy occurring within six months of the last delivery holds a 7.5-fold increased risk for induced abortion and a 1.6-fold increased risk of stillbirth.In a recent study of postpartum unintended pregnancies 86% resulted from non-use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In study carried out by Jani PS, abdominal pain was the major complication of PPIUCD followed by bleeding problem. 6 Shukla et al, reveal that no women complained of pain in lower abdomen or signs of pelvic infection at 6 week follow up. 3 Kumar S et al, mentioned that 8.9% had abdominal pain and 5.5% at menstrual problem after insertion of IUD at 6 week.…”
Section: Discussionmentioning
confidence: 98%
“…In study carried out by Jani PS, abdominal pain was the major complication of PPIUCD followed by bleeding problem. 6 Shukla et al, reveal that no women complained of pain in lower abdomen or signs of pelvic infection at 6 week follow up. 3 Kumar S et al, mentioned that 8.9% had abdominal pain and 5.5% at menstrual problem after insertion of IUD at 6 week.…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted at a hospital in India, 600 women who inserted the copper IUD in the immediate postpartum period were followed for six months; 45 (7.5%) presented some complication after six months being pain (1%), bleeding (0.7%), fall out (0.83%), string loss (1.2%), disorders (3.83%), and 555 (92.5%) had no complications (23) . In this context, the results in the studies cited are in line with the findings in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning IUD removal during the follow-up of 600 women for six months in India, it was found that, among the 37 cases (6.2%), the reasons for removal were pain (1.7%), infection (1, 3%), bleeding (1.5%), fall out (1.3%), and tubal ligation (0.3%); thus, the IUD continuation rate after six months was 93.8% (23) .…”
Section: Discussionmentioning
confidence: 99%
“…13 In other studies the average age was noted to be <30years. 14,15 Understandably the acceptance rate for PPIUCD is higher among primiparous women who would like to avoid another pregnancy soon. In our study 58.3% of the women were para 1.…”
Section: Discussionmentioning
confidence: 99%